Convolutional neural network for assisting accuracy of personalized clavicle bone implant designs - Mayasari, Dita Ayu; Hawari, Ihtifazhuddin; Dwiyanti, Sheba Atma; Noviyadi, Nathasya Reinelda; Andryani, Dinda Syaqila; Utomo, Muhammad Satrio; Hikmah, Nada Fitrieyatul; Asmaria, Talitha (Institute of Advanced Engineering and Science, 2024)
The clavicle is a long bone that tends to be frequently fractured in the midshaft region. The plate and screw fixing method is mainly applied to address this issue. This study aims to construct a clavicle bone implant design with a consideration to achieve a high accuracy and high-quality surface between the plate and the clavicle surface. The computational tomography scanning (CT-scan) image series data were processed using a convolutional neural network (CNN) to classify the clavicle image. The CNN outcomes were gathered as three-dimensional (3D) volume data of clavicle bone. This 3D model was then proposed for the plate design. The CNN testing results of 97.4% for the image clavicle bones classification, whereas the prints of the 3D model from clavicle bone and its plate and screw design reveal compatibility between the bone surface and the plate surface. Overall, the CNN application to the series of CT images could ease the classification of clavicle bone images that would precisely construct the 3D model of clavicle bone and its suitable clavicle bone plate design. This study could contribute as a guideline for other bone plate areas that need to fit the patient’s bone geometry.